The Royal Chapel During the Reign of King João I (1385-1433): the Role of its Clergymen - Coelho, Maria Helena da Cruz (2015)
In this work we will study essentially the ecclesiastical members of king João I’s royal chapel. We will begin by presenting a list containing the number and category of the clerics who constituted it, and their respective salaries. We discriminate the functions of its principal members - head chaplain, singers, almoner – and give particular attention to the king’s confessors, recruited among the mendicant friars, who played a fundamental role in the court’s adoption of lines of spirituality and devotion, as well as in the kingdom’s politics, due to their proximity to the king and the royal family. We then take a closer look at the political-religious dimension of this organ, stressing the infl uence exerted by those clergymen on the king – both at the personal level, acquiring assets, positions, benefi ts and privileges, and in their contribution to defi ning and carrying out the kingdom’s policies.